Current issues in the prevalence, diagnosis and management of hepatocellular carcinoma in Australia. Issue 2 (25th February 2021) - Lubel, John S.; Roberts, Stuart K.; Howell, Jessica; Ward, James; Shackel, Nichols A.
Abstract: Hepatocellular carcinoma (HCC) is the commonest primary liver cancer encountered in the community and a leading cause of cancer morbidity and mortality. In Australia, there are several current important issues that need to be addressed in HCC management. There is a dramatically rising incidence of HCC in Australia with comparatively poorer outcomes in remote regions and in socioeconomic disadvantaged groups. Aboriginal people have a greater incidence of HCC on a background of increased liver disease prevalence and face several barriers to delivery of better healthcare outcomes compared to other Australians. The previously adopted use of imaging alone to diagnose HCC is now being challenged with biopsy likely to become increasingly necessary with the increased uptake of personalised medicine management. Managing HCC is complex involving many disciplines with the multidisciplinary team approach being the current accepted standard of care for patients. New immunotherapy combinations promise to offer patients with advanced HCC promising novel management options. However, the Australian inequities in prevalence, diagnosis and service provision, especially in Aboriginal people, need to be redressed concurrently with the adoption of new HCC management options.